Changes in the Scheme from Production Sharing Contracts to Gross Split for Upstream Oil and Gas Investments in Indonesia - Jody Rabbani Hidayat; Wuryandari, Utji Sri Wulan; Djaelani, Fahmi Ardhi (Dinasti Research, 2025)
This study analyzes the impact of the change in contract scheme from production sharing to Gross Split on investment in Indonesia's upstream oil and gas sector using a normative juridical approach. This policy transformation represents the government's response to the administrative complexity and uncertainty inherent in conventional production sharing contract schemes that have been in place for more than five decades. The research method uses content analysis of laws and regulations, policy documents, and related literature to evaluate the effectiveness of the Gross Split scheme implementation. The results show that the implementation of Gross Split has succeeded in creating a simpler, more transparent, and more predictable regulatory framework compared to the previous system. The elimination of complex cost recovery mechanisms has reduced regulatory uncertainty and accelerated investment decision-making. An evaluation of the investment climate indicates increased exploration activity, improved cash flow predictability, and enhanced access to financing for contractors. However, challenges remain in adaptation challenges, the complexity of split factors, and market acceptance that require continuous improvement. The study recommends the development of a systematic review mechanism, strengthening of regulatory infrastructure, and increasing scheme flexibility to optimize Indonesia's competitiveness in attracting global oil and gas investment. The Gross Split scheme has the potential to become a leading model for sustainable upstream oil and gas sector management.